Single-Phase Single-Stage PV-Grid System Using VSI Based on Simple Control Circuit - Slamet Riyadi (Institute of Advanced Engineering and Science, 2013)
Integrating electric energy generated by PV with utilities has been developed. Some of these using two-stage converters and the others using single stage converters. For systems with two-stage converters, the first stage converter acts as a MPPT to maximize power generated by PV and the second stage is used as an interface to the utilities. In the single-stage system, an inverter is used for both function. In this paper, PV-Grid System using a single-stage Voltage Source Inverter is proposed. The simple control circuit to make PV generate maximum power and keeping power equilibrium between PV and inverter output power is used. To verify the analysis, simulations are done.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1860